Enhancing emulsion, texture, rheological and sensory properties of plant-based meat analogs with green tea extracts - Jong Hyeon Han; Dong Hyun Keum; Vahinika Kothuri; Yea-Ji Kim; Hyuk Cheol Kwon; Do Hyun Kim; Hyun Su Jung; Sung Gu Han (Food Chemistry: X)
Plant-based meat analogs require improvements in taste and texture to better replicate traditional meat. L-theanine and tannin, abundant in green tea, influence food taste and physicochemical properties. This study evaluated the quality characteristics of green tea extract (GE)-supplemented plant-based patties (PP) and the mechanisms affecting taste and texture. Green tea was extracted with water (GWE) or 70 % ethanol (GEE). GEE contained higher tannin and lower L-theanine levels than GWE. Both GWE and GEE reduced protein deterioration and lipid oxidation in PP throughout the 28-day storage period. PP with 1.0 % GEE (PP-GEE1.0) showed improved emulsion stability and texture due to non-covalent interactions including hydrophobic interaction and hydrogen bonds, and increased β-sheet structures between tannin and pea protein. PP-GEE1.0 also had superior sensory characteristics due to an optimal balance of L-theanine and tannin. Overall, the incorporation of GE, particularly GEE significantly improved physicochemical properties, sensory quality, and storage stability of PP.